A multicentre validation study for the EU‐TIRADS using histological diagnosis as a gold standard. (3rd May 2019) - Trimboli, Pierpaolo; Ngu, Rose; Royer, Benedicte; Giovanella, Luca; Bigorgne, Claude; Simo, Ricard; Carroll, Paul; Russ, Gilles
Abstract: Objective: Many systems for risk stratification of thyroid nodule with ultrasound (US) have been proposed and the EU‐TIRADS issued by the ETA in 2017 was the last to have been published. The present study was undertaken to evaluate whether the malignancy risk of each category corresponded to the given range of the guidelines and assess the diagnostic value of EU‐TIRADS in a multi‐institutional trial with histology as gold standard. Design: Three institutions in Switzerland, France and United Kingdom shared this retrospective study. Enrolment period was 2013‐2017. Included were patients who had undergone surgery with a detailed preoperative thyroid US. Methods: Cancer risk was calculated for each EU‐TIRADS score. Predictivity tests were estimated. Nonparametric statistical analysis was used. Results: The final series included 1058 nodules of which 257 (24.3%) carcinomas. Nodules were classified as EU‐TIRADS 2, 3, 4 and 5 in 6.7, 46.4, 26.2 and 20.7%, respectively. Cancer prevalence was 1.4, 3.5, 17 and 87.7% in classes 2‐5, respectively ( P < 0.0001). EU‐TIRADS 5 had a significantly higher cancer rate than the other summed categories (7.7%; P < 0.0001) with OR 84.7. When EU‐TIRADS 4 and 5 were combined, 93% sensitivity and 97% NPV were found and findings of the three institutions were quite similar. Using the recommended criteria for FNA negative predictive value was 90.9%. Conclusions: The cancer rate was within or close to the given range described in the EU‐TIRADS guidelines. The diagnostic value was satisfactory. The results were similar in the three institutions participating in the study.